The algebraic geometry of perfect and sequential equilibrium: an extension - Luo, Xiao; Qian, Xuewen; Sun, Yang (Springer, 2020)
We extend the generic equivalence result of Blume and Zame (Econometrica 62: 783-794, 1994) to a broader context of perfectly and sequentially rational strategic behavior (including equilibrium and nonequilibrium behavior) through a unifying solution concept of "mutually acceptable course of action" (MACA) proposed by Greenberg et al. (2009). As a by-product, we show, in the affirmative, Dekel et al.'s (1999) conjecture on the generic equivalence between the sequential and perfect versions of rationalizable self-confirming equilibrium. JEL Classification: C70, C72